JUSTIFICATION OF MUTUALLY DETERMINED FACTORS IN THE FORMATION OF THE INTERNAL SYSTEM OF THE MORAL IDEAL OF YOUTH (КЫРГЫЗ РЕСПУБЛИКАСЫНЫН УЛУТТУК ИЛИМДЕР АКАДЕМИЯСЫНЫН КАБАРЛАРЫ, 2023)
This article presents ideas that the creation of a high exemplary spiritual and moralsystem, based on the requirements of high principles of the moral ideal, is a guarantee of survivalfrom disasters similar to the current “mass culture”. The article, taking into account that strengthening the moral and aesthetic culture of youth is a pedagogical, philosophical and sociologicalproblem, provides a philosophical understanding of the constructive relationship between the defining, governing and controlling functions of the moral ideal in the emerging moral and aestheticculture of youth, substantiates the mutually determining factors in the formation of the internalsystem of moral ideal of personality.